The Effect of Letter Transposition on Reading Comprehension - Bruce, Megan (My University, 2015)
This study examined the effect of letter transposition on reading comprehension. Since reading comprehension depends heavily on word recognition, by measuring the efficiency of reading comprehension, insight can be gained as to whether consonants or vowels are used as more important landmarks when distinguishing words. Previous research has shown that transposed letter (TL) non-words are processed quicker than replacement letter (RL) non-words. The results of this study indicate that there is no significant difference overall between the processing speed of sentences with transposed consonants and sentences with transposed vowels, though the data do indicate a trend toward processing occurring faster when vowels were transposed. However, though processing speed was faster, accuracy of remembering the sentence was lower. This is commonly referred to as the speed/accuracy tradeoff.